miR-524-5p reduces the progression of the BRAF inhibitor-resistant melanoma - Nguyen, Mai-Huong Thi; Lin, Chen-Huan; Liu, Szu-Mam; Miyashita, Azusa; Ihn, Hironobu; Lin, Hsuan; Ng, Chi Hou; Tsai, Jen-Chieh; Chen, Ming-Hong; Tsai, Mu-Shiun; Lin, In-Yu; Liu, Shu-Chen; et al. (Neoplasia (New York, N.Y.), 2020)
BRAF inhibitors were approved for the treatment of BRAF-mutant melanoma. However, most patients acquire the resistance to BRAF inhibitors after several months of treatment. miR-524-5p is considered as a tumor suppressor in many cancers, including melanoma. In this study, we investigated the biological functions of miR-524-5p in melanoma with acquired resistance to BRAF inhibitor and evaluated the endogenous miR-524-5p expression as a biomarker for melanoma. The results showed that the expression of miR-524-5p was 0.481-fold lower in melanoma tissues (n = 117) than in nevus tissues (n = 40). Overexpression of miR-524-5p significantly reduced proliferative, anchorage-independent growth, migratory and invasive abilities of BRAF inhibitor-resistant melanoma cells. Moreover, the introduction of miR-524-5p led to a reduced development of BRAF inhibitor-resistant melanoma in vivo. Remarkably, the MAPK/ERK signaling pathway was decreased after treatment with miR-524-5p. Furthermore, next-generation sequencing analysis implied that the complement system, leukocyte extravasation, liver X receptor/retinoid-X-receptor activation, and cAMP-mediated signaling may be related to miR-524-5p-induced pathways in the resistant cells. The miR-524-5p level was higher on average in complete response and long-term partial response patients than in progressive disease and short-term partial response patients treated with BRAF inhibitors. Our results proposed that miR-524-5p could be considered as a target for treatment BRAF inhibitor-resistant melanoma and a prognostic marker in the response of patients to BRAF inhibitors for melanoma.